Ethnomathematics Exploration of Malay Traditional Clothing Patterns in the Concept of Two-Dimensional Plane Figure - Amelia, Nurul; Lubis , Nur Ainun (Unnes Journal of Mathematics Education, 2024)
Ethnomathematics is a field that studies how people from different cultures understand, interpret, and use mathematical concepts. Traditional clothing is one of the cultural characteristics of the local community. The motifs on Malay traditional clothing depict symbols, ideas, and techniques of plane figures, often used intuitively by seamstresses. These motifs can be found in various Malay traditional garments and have a connection to ethnomathematics, particularly in measuring activities and mathematical concepts based on two dimensions. Therefore, the purpose of this study was to explore the elements and concepts of plane figures in Malay traditional clothing patterns through an ethnomathematics perspective. This research employs qualitative methods, with data collection conducted through observation, interviews, documentation, and literature review. The study was exploratory in nature, utilizing an ethnographic approach. The findings reveal that the motifs in Malay traditional clothing patterns, which include elements and concepts of two-dimensional shapes such as rhombuses, circles, triangles, and squares, can serve as a valuable learning resource for understanding two-dimensional geometry.